(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Menopause is the complete cessation of menstrual cycle for 12 consecutive months without undergoing any surgical measures is considered as menopause for women. Women experiences lots of physical discomforts during menopause due to the changes in the physiological and psychological state. Certain poses of yoga are rewarding in reducing the difficulties causing by menopause. As the body experiences menopausal changes such as degeneration of joints and muscle loss can be reduced by certain yoga poses. Yoga also reduces the emotional symptoms. The study was done to enhance the knowledge of yoga therapy on menopausal problems among the women with the age group of 40 to 55 years by educating them with the help of pamphlet and videos. Researcher used non experimental approach and descriptive survey method for this study. Data collection was don froe 60 women residing in the villages of Shimoga by using the tool contains social demographic data and questionnaire to assess the knowledge on yoga theory on menopausal problems. At the end the results depicted that women having adequate knowledge 58%regarding yoga therapy on menopausal problems, about 23% having moderate knowledge and about 18% inadequate knowledge on the same Menopause is the complete cessation of menstrual cycle for 12 consecutive months without undergoing any surgical measures is considered as menopause for women. Women experiences lots of physical discomforts during menopause due to the changes in the physiological and psychological state. Certain poses of yoga are rewarding in reducing the difficulties causing bymenopause. As the body experiences menopausal changes such as degeneration of joints and muscle loss can be reduced by certain yoga poses. Yoga also reduces the emotional symptoms. The study was done to enhance the knowledge of yoga therapy on menopausal problems among the women with the age group of 40 to 55 years by educating them with the help of pamphlet and videos. Researcher used non experimental approach and descriptive survey method for this study. Data collection was don froe 60 women residing in the villages of Shimoga by using the tool contains social demographic data and questionnaire to assess the knowledge on yoga theory on menopausal problems. At the end the results depicted that women having adequate knowledge 58%regarding yoga therapy on menopausal problems, about 23% having moderate knowledge and about 18% inadequate knowledge on the same